Principal Management in Developing Student Character - Octarina, Rizqa; Rambun; Juliwis Kardi (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2025)
Good student character is one of the benchmarks of the principal's success in fostering students in schools today. Producing students with good character is certainly a challenge for educational stakeholders, especially principals. The role of the principal is very important in fostering good behavior patterns in students at school, so that the output of character development can be felt by those around them. This study aims to analyze how the principal's role in fostering student character. This study uses a qualitative method with a case study design approach. Data sources were collected through in-depth interviews with the principal, teachers, and education staff. In addition, direct observations were also conducted at the school and analyzed documents related to this research. In this study, it was found that the principal implemented several things in fostering student character. First, the principal carried out character development directly with students by providing exemplary examples, advising and reprimanding undisciplined teachers. Indirectly, character development was carried out by all educators at SMA IT Darul Hikmah Pasaman Barat, establishing cooperation with various parties in fostering student character such as cooperation between Islamic religious education teachers and general study teachers. Second, the principal controls and supervises the development of students' morals through all teachers. Third, the principal evaluates students' moral development by administering punishments or sanctions that are designed to build their character. The principal's management of student character development can serve as a reference for principals in developing student character in educational institutions.